Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijms22168597
|View full text |Cite
|
Sign up to set email alerts
|

Enriched Alternative Splicing in Islets of Diabetes-Susceptible Mice

Abstract: Dysfunctional islets of Langerhans are a hallmark of type 2 diabetes (T2D). We hypothesize that differences in islet gene expression alternative splicing which can contribute to altered protein function also participate in islet dysfunction. RNA sequencing (RNAseq) data from islets of obese diabetes-resistant and diabetes-susceptible mice were analyzed for alternative splicing and its putative genetic and epigenetic modulators. We focused on the expression levels of chromatin modifiers and SNPs in regulatory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 53 publications
(73 reference statements)
2
4
0
1
Order By: Relevance
“…Secondly, exposure of human islets to mildly elevated glucose concentrations led to increased SRRM3 expression and IsletMIC inclusion, suggesting an adaptive mechanism to modulate insulin secretion in a setting that has the potential to enhance secretion. Finally, we also observed that IsletMICs are broadly down-regulated in islets from T2D patients, an effect also recently reported in a diabetic mouse model 27 . Altogether, these data suggest that changes in the activity of SRRM3 and its microexon targets affect islet function and glucose homeostasis, potentially contributing to T2D predisposition.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Secondly, exposure of human islets to mildly elevated glucose concentrations led to increased SRRM3 expression and IsletMIC inclusion, suggesting an adaptive mechanism to modulate insulin secretion in a setting that has the potential to enhance secretion. Finally, we also observed that IsletMICs are broadly down-regulated in islets from T2D patients, an effect also recently reported in a diabetic mouse model 27 . Altogether, these data suggest that changes in the activity of SRRM3 and its microexon targets affect islet function and glucose homeostasis, potentially contributing to T2D predisposition.…”
Section: Discussionsupporting
confidence: 87%
“…A similar pattern was also found in islets from diabetes-susceptible NZO mice following a diabetogenic stimulus (Extended Data Fig. 6E) 27 . Importantly, down-regulation of IsletMICs was unlikely to be due to beta cell loss, as we also observed it in individuals with impaired glucose tolerance (Extended Data Fig.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“… 34 Associations have been observed between three RNA‐binding proteins and insulin resistance; therefore, increased type 2 diabetes risk. 35 , 36 Hence, the authors hypothesized an association between elevated RNA‐binding protein subunit (#38) levels and diabetic renal complications in T1DM patients with DN. 37 …”
Section: Rbps In Diabetic Nephropathymentioning
confidence: 99%
“…RNA‐binding protein regulatory subunit 38, also known as Protein DJ‐1, is likely to be significantly more abundant in T1DM patients with DN due to specific mRNAs stabilization, a process by which cells may control protein expression levels 34 . Associations have been observed between three RNA‐binding proteins and insulin resistance; therefore, increased type 2 diabetes risk 35,36 . Hence, the authors hypothesized an association between elevated RNA‐binding protein subunit (#38) levels and diabetic renal complications in T1DM patients with DN 37 …”
Section: Rbps In Diabetic Nephropathymentioning
confidence: 99%